An evaluation of the difference in the persentation and treatment response of Tuberculosis in HIV and TB sputum positive patients : Haart versus pre-Haart era - Rheeder, Paul (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.